A Review of Mild Combustion and Open Furnace Design Consideration - M. M., Noor; Wandel, Andrew P.; Yusaf, Talal (Universiti Malaysia Pahang, 2012)
Combustion is still very important to generate energy. Moderate or Intense Low-oxygen Dilution (MILD) combustion is one of the best new technologies for clean and efficient combustion. MILD combustion has been proven to be a promising combustion technology in industrial applications with decreased energy consumption due to the uniformity of its temperature distribution. It is clean compared to traditional combustion due to producing low NOx and CO emissions. This article provides a review and discussion of recent research and developments in MILD. The issue and applications are summarized, with some suggestions presented on the upgrading and application of MILD in the future. Currently MILD combustion has been successfully applied in closed furnaces. The preheating of supply air is no longer required since the recirculation inside the enclosed furnace already self-preheats the supply air and self-dilutes the oxygen in the combustion chamber. The possibility of using open furnace MILD combustion will be reviewed. The design consideration for open furnace with exhaust gas re-circulation (EGR) was discussed.